A synbiotic supplement for inflammation and oxidative stress and lipid abnormalities in hemodialysis patients. Issue 2 (1st March 2019) - Kooshki, Akram; Tofighiyan, Tahereh; Miri, Mohammad
Abstract: Introduction: Among the most important risk factors for cardiovascular disease in hemodialysis patients are high concentrations of serum inflammation markers, lipid profiles, and oxidative stress. The present study aimed to investigate the effects of a synbiotic supplement on serum systemic inflammation, oxidative stress markers, and lipid profile in hemodialysis patients. Methods: Fifty hemodialysis patients were randomly allocated to synbiotic and placebo groups. The synbiotic group received 2 tablets per day of a synbiotic supplement (100 mg) Lactobacillus coagulans and fructo‐oligosaccharides for 8 weeks; whereas the placebo group received a similar appearing placebo. At the beginning and end of the study, 5 mL blood was taken after 12–14 hours of fasting. Findings: Mean values of serum C‐reactive protein (hs‐CRP) and malondialdehyde (MDA) significantly decreased in the synbiotic group at the end compared to the beginning of the study (P = 0.01). This reduction was significant in comparison with changes in the placebo group (P = 0.01). The synbiotic supplement also reduced serum total cholesterol (P = 0.001) and low‐density lipoprotein cholesterol (LDL‐c; P = 0.001) compared to the placebo group. Discussion: The synbiotic supplement used improves serum hs‐CRP and MDA, total cholesterol and LDL‐c in hemodialysis patients, which are known risk factors for cardiovascular disease.